2017
DOI: 10.4269/ajtmh.17-0131
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Complications of Plasmodium vivax Malaria: Systematic Review and Meta-Analysis

Abstract: Malaria, a major global public health problem, is mainly caused by and, and is responsible for nearly half a million deaths annually. Although malaria was not believed to cause severe disease, recent robust studies have proved otherwise. However, the clinical spectrum and pathogenesis of severe vivax malaria and, especially, its respiratory complications remain poorly understood. A systematic search for articles reporting respiratory complications associated with vivax malaria was performed in Lilacs, Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 131 publications
1
34
0
2
Order By: Relevance
“…vivax patients were treated with Chloroquine, including the 138 who had initiated treatment at the POC, before enrolment at the hospital. In our series, Chloroquine pre-treatment appear to associate with any particular malaria complication, as previously suggested [ 48 ].…”
Section: Discussionsupporting
confidence: 85%
“…vivax patients were treated with Chloroquine, including the 138 who had initiated treatment at the POC, before enrolment at the hospital. In our series, Chloroquine pre-treatment appear to associate with any particular malaria complication, as previously suggested [ 48 ].…”
Section: Discussionsupporting
confidence: 85%
“…A pooled analysis of clinical studies since the year 1900 describing complications in vivax patients showed a 0.27% prevalence of respiratory dysfunction in reports with and without severity signs [ 10 ]. Geographical stratification has shown that prevalence estimates of respiratory complications vary according to endemic regions [ 11 ], mostly due to a complex interplay of host and vector characteristics [ 9 ]. Nonetheless, part of the variation is because of definitions used to describe these respiratory complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported cases of respiratory complications in vivax malaria after treatment [ 11 ], with a tenfold increase in the risk for developing respiratory distress [ 8 ]. It is suggested that a post-treatment inflammatory phenomenon occurs within lung microvasculature in these cases leading to respiratory impairment [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the great majority of malaria cases occur in the Amazon region, with Plasmodium vivax beingresponsible for nine out of every ten cases [1]. Although severe malaria has been historically associated to P. falciparum infection,an increasing number of reports has demonstrated the association between vivax malaria mono-infections and adverse outcomes [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%